Long-Term Use of Antibiotics and Risk of Parkinson’s Disease in the Nurses’ Health Study - Natalia Palacios; Éilis J O’Reilly; Michael A. Schwarzschild; Alberto Ascherio (Parkinson's Disease)
Objective. Antibiotic use is one of the strongest environmental predictors of an altered and less diverse gut microbiome, which has been linked to Parkinson’s disease. To our knowledge, no prior study has examined the association between long-term antibiotic use and Parkinson’s disease. Design. We conducted a prospective study of 59,637 women in the Nurses’ Health Study who reported total duration of antibiotic use at ages 20–39, 40–59, 60 +, or during the past 4 years. We used Cox Proportional Hazard regression to estimate hazard ratios and 95% confidence intervals for the association between categories of antibiotic use and risk of PD. Results. One hundred and eighty cases of PD were confirmed during the follow-up. Self-reported antibiotic use at ages 20–39, 40–59, and 60 +, as assessed in 2004, was not significantly associated with PD risk in our cohort. The hazard ratio comparing participants who used antibiotics for 2 or more months vs. 1–14 days at age 20–39 was 0.98 (95% CI: 0.54, 1.78), at age 40–59 was 1.44 (95% CI: 0.88, 2.33), and at age 60 +was 0.88 (95% CI: 0.53, 1.47). Antibiotic use during the past four years, as assessed in 2008, was also not associated with future risk of PD (HR: 1.14, 95% CI: 0.62, 2.10). Conclusion. In this cohort study, we did not observe a significant association between antibiotic use and incidence PD. A major limitation of our study is assessment of exposure, which required many participants to recall their antibiotic use decades in the past. Thus, although the results of this study do not support an effect of antibiotic use on PD risk, larger investigations relying on records of antibiotic prescriptions would provide more definitive evidence.